Assessment of earthquake resistance of critical infrastructure objects, taking into account their own harmonics in the explosive spectrum of civil and military characters - V.V. Boiko; Yu.I. Voitenko; A.L. Han; T.V. Khlevniuk; Ye.A. Zahoruiko; O.V. Han (Технічна інженерія)
The article presents theoretical and experimental studies of the patterns of repeatability of seismic waves excited by man-made explosions to assess the earthquake resistance of critical infrastructure objects. The nature of propagation of wave perturbations at the boundary of an elastic half-space during its local excitation is theoretically considered. These studies are based on the integral Laplace and Fourier transformations, the numerical solution of which makes it possible to obtain the values of the repetition periods of elastic wave perturbations at the half-space boundary. On the basis of theoretical studies, the regularity of periods of repetition of perturbations of elastic waves is established, which under certain conditions can create resonant phenomena in protected objects, in particular at a harmonic close to the frequency of natural vibrations of the structure. Confirmation of these results in practice was obtained when critical infrastructure was hit by missile strikes (Kyiv TV tower tower) and in the conditions of blasting operations at quarries, as an example at the Koshchiivske granite quarry of LLC "SIPAN" when assessing the earthquake resistance of critical infrastructure objects, in particular the supports of 330 kW power lines, which are located in the zone of influence of elastic waves. They are based on the formation of patterns of excitation and propagation of elastic waves and determination of their parameters at a distance from the source of excitation (mass explosions at the quarry) using a hardware complex of standard seismic sensors SM-3, a 16-channel analog-to-digital converter (ADC E14-440) of L-Card and a personal computer (PC). Assessment of the influence of the intensity of seismic explosion waves was carried out at the frequency of the amplitude of the maximum speed of vibrations both at the base of the support, which is the norm of seismic safety in accordance with DSTU 4704:2008 and in the structure of the support itself (which is not mandatory in accordance with DSTU 4704:2008). But the presence of harmonics in the explosive spectrum that is close to the natural vibrations of the structure leads to the formation of resonant phenomena in it, which leads to an increase in the speed of vibrations in the structure itself than in the base of the support. Therefore, the maximum speed at a frequency close to its own vibrations or at the base of the support or on its structure is taken as a criterion of seismic safety. Such a wave parameter will best correlate with damage or harm to this structure and was proposed as the norm of its earthquake resistance. The research results obtained in this way prompted the authors to propose a supplement to the current DSTU.